Phase 4 Pharmacovigilance Trial of Paromomycin Injection for the Treatment of Visceral Leishmaniasis in India - Prabhat K. Sinha; T. K. Jha; Chandreshwar P. Thakur; Devendra Nath; Supriyo Mukherjee; Amrendra Kumar Aditya; Shyam Sundar (Journal of Tropical Medicine)
Background. A phase 3 study demonstrated the safety and efficacy of paromomycin (paromomycin IM injection) for treatment of VL in an inpatient setting. Methods. This phase 4 study was conducted to assess the safety and efficacy of paromomycin in children and adults in an outpatient setting in Bihar, India. Results. This study enrolled 506 adult and pediatric patients. Of the 494 patients in the intent-to-treat (ITT) population, 98% received a full course of treatment. The overall study completion rate was 94% (462/494) for the ITT population and 96% (461/479) for the efficacy-evaluable (EE) population. Initial clinical cure was 99.6%, and final clinical cure 6 months after treatment was 94.2%. Grade 3 or 4 adverse events occurred in 5% of patients; events with a frequency of ≥1% were increases in alanine aminotransferase and aspartate aminotransferase. Conclusions. This study confirms the safety and efficacy of paromomycin to treat VL in an outpatient setting.